Perancangan dan Penerapan Strategi Promosi atau Membangun Brand Image melalui Media Digital dan Pelatihan pada UMKM Caukong - Teddy Ricardo; Nasar Buntu Laulita (Cv. Utility Project Solution, 2022)
Caukong is an MSME engaged in the culinary field that sells a variety of foods that are often the daily meal of Indonesian people. Over the years in running its business, Caukong MSMEs have only used word of mouth promotions so that they only reach a few customers which has an impact on Caukong MSME sales. Therefore, it takes a number of promotional strategies or branding to increase sales. In practical the authors use observation and interviews to collect the required data. The outputs produced in this activity are creating Instagram social media accounts and Google profile business, conducting digital advertisements through the Instagram ads feature, designing logos, digital menu cards, creating Instagram content and creating modules related to how to manage social media for promotion and advertising. In its implementation, Caukong MSMEs have not been able to utilize social media for promotion or improve their performance. So that through this practical work activity, implementation was carried out with the result that Caukong's MSME sales grew. Recommendations for further research are that Caukong MSMEs consistently use social media for advertising or promotion.